2018
DOI: 10.1002/syn.22077
|View full text |Cite
|
Sign up to set email alerts
|

Extensive exploration of a novel rat model of Parkinson's disease using partial 6‐hydroxydopamine lesion of dopaminergic neurons suggests new therapeutic approaches

Abstract: Parkinson's disease (PD) is characterized by the degeneration of dopaminergic (DA) neurons constituting the nigrostriatal pathway. Neuroinflammation, related to microglial activation, plays an important role in this process. Exploration of animal models of PD using neuroimaging modalities allows to better understand the pathophysiology of the disease. Here, we fully explored a moderate lesion model in the rat in which 6‐hydroxydopamine was unilaterally delivered in three sites along the striatum. The degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…For this purpose, we performed in a first step in rats, an extensive test-retest study that demonstrated the ability of [ 18 F]LBT-999 to quantify the DAT with high reproducibility (variability of 8–14%) and reliability (intra-class correlation coefficient, ICC, of 0.9) in the striatum, whereas these parameters were less accurate in the substantia nigra, in relation with the small size of this brain structure (33). In a rat model of early PD induced by a moderate unilateral striatal lesion using 6-hydroxydopamine (6-OHDA), we showed that [ 18 F]LBT-999 was able to accurately quantify in vivo the dopaminergic endings loss (Figure 2), in full agreement with the results obtained by in vitro autoradiography with [ 125 I]PE2I on brain sections (34).…”
Section: Preclinical Experiments In Animal Modelssupporting
confidence: 78%
“…For this purpose, we performed in a first step in rats, an extensive test-retest study that demonstrated the ability of [ 18 F]LBT-999 to quantify the DAT with high reproducibility (variability of 8–14%) and reliability (intra-class correlation coefficient, ICC, of 0.9) in the striatum, whereas these parameters were less accurate in the substantia nigra, in relation with the small size of this brain structure (33). In a rat model of early PD induced by a moderate unilateral striatal lesion using 6-hydroxydopamine (6-OHDA), we showed that [ 18 F]LBT-999 was able to accurately quantify in vivo the dopaminergic endings loss (Figure 2), in full agreement with the results obtained by in vitro autoradiography with [ 125 I]PE2I on brain sections (34).…”
Section: Preclinical Experiments In Animal Modelssupporting
confidence: 78%
“…Moreover, the neuroprotective properties of acetylcarnitine have been found in rats treated with 6-OHDA [175,176,177] and rotenone [178,179], and non-human primates treated with MPTP [180]. Additionally, increased levels of carnitine and acylcarnitine 16:0 and 18:0 have been detected in the striatum of 6-OHDA-treated rats and the mesencephalon of MPTP-treated mice, respectively [181,182], suggesting a compensatory mechanism against PD-associated toxicity. Thus, while it remains unclear whether the levels of acylcarnitine change in PD patients, mounting evidence points towards decreased plasma levels and a protective role of acylcarnitine in animal and cellular PD models.…”
Section: Fatty Acylsmentioning
confidence: 99%
“…Vetel et al also found the specific retention of [ 3 H]DPA-714 in the ipsilateral striatum was significantly higher than that in the contralateral striatum on day 14 p.l. [21]. Besides, previous clinical PET imaging using [ 11 C]PK11195 revealed a high uptake in the brain of PD patients due to the activated microglia [11, 12].…”
Section: Discussionmentioning
confidence: 99%